Refugees in Egypt: practices and prospective law. - Sharafeldin, Neemat (AUC Knowledge Fountain, 2020)
The lack of a unified Egyptian asylum law has led to the existence of fragmented policies governing refugees in Egypt, this in turn caused ambivalence and inconsistencies in the implementation of any existing laws pertaining to refugee governance. Consequently, these inconsistencies have affected some of the rights that refugees should enjoy according to the 1951 Refugee convention, including access to healthcare, education, the formal labor market as well as the denial of long-term residency permits for refugees in Egypt, among other rights. Accordingly, this research first, aims to review the most important documents shaping the Egyptian legal framework regarding refugees, as well as identify the gaps between the Egyptian government’s policies towards refugees and their implementation. The research also seeks to offer possible remedial policies and recommendations, proffered by experts in the field, on how these gaps could be properly addressed. Finally, the paper addresses the draft asylum law announced recently by the Egyptian government and reviews the possible reasons behind its proposition and then analyses the priority areas that should be addressed in the new asylum law.